Combined modeling of cell aggregation and adhesion mediated by receptor–ligand interactions under shear flow. Issue 6 (November 2015) - Du, Yu; Peng, Shuang; Cui, Yuhong; Lü, Shouqin; Zhang, Yan; Long, Mian
Abstract: Blood cell aggregation and adhesion to endothelial cells under shear flow are crucial to many biological processes such as thrombi formation, inflammatory cascade, and tumor metastasis, in which these cellular interactions are mainly mediated by the underlying receptor–ligand bindings. While theoretical modeling of aggregation dynamics and adhesion kinetics of interacting cells have been well studied separately, how to couple these two processes remains unclear. Here we develop a combined model that couples cellular aggregation dynamics and adhesion kinetics under shear flow. The impacts of shear rate (or shear stress) and molecular binding affinity were elucidated. This study provides a unified model where the action of a fluid flow drives cell aggregation and adhesion under the modulations of the mechanical shear flow and receptor–ligand interaction kinetics. It offers an insight into understanding the relevant biological processes and functions. Highlights: Combine the dynamics of cell aggregation and adhesion under shear flow. Parametric analysis of cell collision and adhesion efficiency. Interplay between cell aggregation and adhesion near the wall.